The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1186/1471-2105-7-365
|View full text |Cite
|
Sign up to set email alerts
|

PIPE: a protein-protein interaction prediction engine based on the re-occurring short polypeptide sequences between known interacting protein pairs

Abstract: Background: Identification of protein interaction networks has received considerable attention in the post-genomic era. The currently available biochemical approaches used to detect protein-protein interactions are all time and labour intensive. Consequently there is a growing need for the development of computational tools that are capable of effectively identifying such interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 41 publications
2
108
0
Order By: Relevance
“…Similarly, Gid8 interacts directly with Gid1 [13]; in addition, gid8 deletion mutants in S. cerevisiae indicated that Gid8 functions as an adapter for Gid2 and Gid9 [13]. An in silico prediction of protein–protein domain interactions in S. cerevisiae implicated a strong involvement of Gid8 within a “core” GID complex: tandem affinity purification of Gid1 and the loss of several Gid1-co-purifying proteins in a Gid8 gene deletion yeast strain (ΔYMR135C) give substance to this hypothesis [27]. Whereas LisH domains from several unrelated proteins have been crystallized [18,24,28] and the LisH domain of muskelin has been crystallized in combination with its N-terminal discoidin domain [29], almost nothing is known about the biochemical properties of TWA1, Gid8 or their orthologues in other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gid8 interacts directly with Gid1 [13]; in addition, gid8 deletion mutants in S. cerevisiae indicated that Gid8 functions as an adapter for Gid2 and Gid9 [13]. An in silico prediction of protein–protein domain interactions in S. cerevisiae implicated a strong involvement of Gid8 within a “core” GID complex: tandem affinity purification of Gid1 and the loss of several Gid1-co-purifying proteins in a Gid8 gene deletion yeast strain (ΔYMR135C) give substance to this hypothesis [27]. Whereas LisH domains from several unrelated proteins have been crystallized [18,24,28] and the LisH domain of muskelin has been crystallized in combination with its N-terminal discoidin domain [29], almost nothing is known about the biochemical properties of TWA1, Gid8 or their orthologues in other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Then, use the gathered information to find correlation with query protein partners of a probed interaction. Many methods apply this approach, which have delivered powerful tools for finding new interactions [Pitre et al 2006] and even to corroborate with the protein co-evolution hypothesis [Kim et al 2004]. In the next three Sections we describe three of these methods: PIPE, which compares aminoacid subsequences between probed protein partners and partners of verified protein interactions from a database; and PSIbase and PRISM, both which compare structural characteristics of probed and verified interactions.…”
Section: Methods Based On Verified Interactionsmentioning
confidence: 99%
“…Another, relatively inexpensive, way to predict protein-protein interactions does not include wet lab analysis, using instead a variety of computational approaches. These approaches can complement experimental wet lab techniques and are often supported by either the hypothesis of protein co-evolution [Tan et al 2004, Tillier et al 2006, Izarzugaza et al 2006], structural similarities [Gong et al 2005, Ogmen et al 2005 or amino-acids sequence conservation [Pitre et al 2006].…”
Section: Current Computational Approaches For Predicting Protein-protmentioning
confidence: 99%
See 1 more Smart Citation
“…Our computational inference makes use of the Protein-protein Interaction Prediction Engine (PIPE), an algorithm that predicts PPIs on the basis of protein primary sequence only [3236]. PIPE breaks query proteins into short overlapping polypeptide segments and searches within a list of known and experimentally verified PPIs to find similar segments.…”
Section: Introductionmentioning
confidence: 99%